SOSIALISASI PEMANFAATAN KEDELAI MENJADI PRODUK TAHU DAN DAMPAKNYA DI KELURAHAN PELAWI UTARA KECAMATAN BABALAN KABUPATEN LANGKAT - Suhardi Napid; Selly Oktaria; Rahmad Setia Budi; Rachmat Rizaldi; Radifa Palevi (Jurnal Pengabdian Mitra Masyarakat, 2022)
North Pelawi Village is one of the villages located in Babalan District, Langkat Regency. Independent enterprises that make tofu are micro, small and medium enterprises that are still active in carrying out activities to produce a tofu product using vinegar at a relatively low cost. The impact of using vinegar for the manufacture of tofu, where the liquid waste can cause environmental pollution because the water flowing in the sewers has a very strong smell, especially if the volume of liquid waste is large, of course it will make people restless and disturb the surrounding environment and the effect of vinegar can cause stomach acid which can bring disease on our bodies. The implementation of the activities is carried out by theoretical and lecture methods (socialization) and the implementation method in which the above student activities are accompanied by DPL lecturers to help the community of North Pelawi Village. The results of the KKN-T activities related to tofu making are carried out through socialization in which it is hoped that the next tofu production must be switched from the use of vinegar to the use of nigarin sea water with the consequence of avoiding environmental pollution and avoiding the tendency of stomach acid and avoiding the tendency of stomach acid. The socialization activity of making tofu has benefits, namely it can increase public knowledge.